Global Trends and Transitions in Security Expertise from nuclear deterrence to climate change and back again - McGann, James G. (Global institutions series)
Tracking the evolution of security as understood by researchers and policymakers is vital as the world follows the path of the Four Mores: more issues, more actors, more competition, and more conflict. As we move forward into a world of rapid change and ubiquitous uncertainty, think tanks will only become more prominent and influential